Case Report: A new case of YARS1-associated autosomal recessive disorder with compound heterozygous and concurrent 47, XXY - Kuan, Janene; Hansen, Ashleigh; Wang, Hua (Frontiers in Pediatrics, 2023)
Aminoacyl-tRNA synthetases play a pivotal role in catalyzing the precise coupling of amino acids with their corresponding tRNAs. Among them, Tyrosyl tRNA synthetase, encoded by the YARS1 gene, facilitates the aminoacylation of tyrosine to its designated tRNA. Heterozygous variants in the YARS1 gene have been linked to autosomal dominant Charcot-Marie-Tooth type C, while recent findings have unveiled biallelic YARS1 variants leading to an autosomal recessive multisystemic disorder in several cases. In this report, we present a novel case characterized by dysmorphic facies, and multisystemic symptoms, prominently encompassing neurological issues and a microarray conducted shortly after birth revealed 47, XXY. Utilizing whole exome sequencing, we uncovered a paternally inherited likely pathogenic variant (c.1099C>T, p.Arg367Trp), previously reported, coinciding with the father's history of hearing loss and neurological symptoms. Additionally, a maternally inherited variant of uncertain significance (c.782T>G, p.Leu261Arg), previously unreported, was identified within the YARS1 gene. The observed phenotypes and the presence of compound heterozygous results align with the diagnosis of an autosomal recessive disorder associated with YARS1.Through our cases, the boundaries of this emerging clinical entity are broadened. This instance underscores the significance of comprehensive genetic testing in patients exhibiting intricate phenotypes.